Drive Scheme and Motion Simulation of the Planetary Stairs-climbing Wheelchair - Fan Xingguang; Li Yi; Jia Liang (Jixie chuandong)
The stairs- climbing wheelchair can be divided into several types according to the principle,including the crawler type,planetary wheel type and foot type,etc. The movement process of planetary stairs-climbing wheelchair is mainly analyzed,and the existing problems of the current stairs- climbing wheelchair is pointed out and a drive scheme which uses the concentric shaft to achieve different drive and can make a wheelchair move more stably is put forward. By using the CATIA software,the design of the structure and motion simulation are carried out,the feasibility of the design scheme is verified.